Normal pedal pulses in a popliteal artery thrombosis after a trampoline-associated knee dislocation: a case report. Issue 4 (10th November 2010) - Harb, Z; Harb, A; Kammoona, Ishan; Huber, C
Abstract : In lower extremity trauma, it is routine to check the neurovascular status of the affected limb. Failure to recognise a vascular injury can have catastrophic consequences for the patient. The frequent observation of the distal pulses at regular intervals after a traumatic knee dislocation is absolutely mandatory for the early recognition and management of popliteal artery thrombosis. A limb-threatening complication of popliteal artery thrombosis occurring in association with a palpable dorsalis pedis pulse after a trampoline-related knee dislocation is reported here to emphasise some important teaching points. These lessons are a learning tool to help in the early recognition of the potential complications associated with such injuries and thus minimise their occurrence.